Creating a Research Ethics Consultation Service: Issues to Consider. Issue 5 (8th September 2021) - Taylor, Holly A.; Porter, Kathryn M.; Paquette, Erin Talati; McCormick, Jennifer B.; Tumilty, Emma; Arnold, Jason F.; Spector‐Bagdady, Kayte; Danis, Marion; Brandt, Debra; Shah, Jina; Wilfond, Benjamin S.; Lee, Lisa M.
Abstract: This article provides pragmatic advice for organizations interested in creating a research ethics consultation service (RECS). A robust RECS has the potential to build capacity among investigators to identify and consider the ethical issues they encounter while conducting their research. Determining whether to establish an RECS should begin with an institutional‐needs assessment that includes three key questions: What are the current resources available to research teams to navigate ethical concerns that arise from their research? Is there a demand or perceived need for more resources? Is there institutional support (financial and otherwise) to establish and maintain an RECS? If this results in the decision to establish the consultation service, relevant institutional stakeholders must be identified and consulted, and personnel with the requisite skills recruited. The next step is to establish an RECS and build the infrastructure to process and respond to requests. The RECS's long‐term sustainability will depend on a stable source of funding and a mechanism to receive constructive feedback to ensure that the service is meeting the institutional needs it set out to address.